1990
DOI: 10.1111/j.1440-1746.1990.tb01432.x
|View full text |Cite
|
Sign up to set email alerts
|

Ispaghula therapy in irritable bowel syndrome: Improvement in overall well‐being is related to reduction in bowel dissatisfaction

Abstract: This placebo controlled, double-blind, cross-over trial involving 20 patients was conducted to assess the effect of ispaghula husk on the major bowel symptoms and the whole gut transit time in irritable bowel syndrome (IBS) and to determine if changes in these parameters were related to global improvement. All 20 patients were interviewed at the end of the treatment periods and 14 patients kept concurrent daily records. Ispaghula therapy resulted in improvement in global symptoms and satisfying bowel movements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 18 publications
1
25
0
1
Order By: Relevance
“…There have been a number of trials of either fiber supplementation or bulking agents for IBS 22,28,30,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] (Table 2). Most of these trials were done between 1976 and 1994.…”
Section: Fiber Trialsmentioning
confidence: 99%
“…There have been a number of trials of either fiber supplementation or bulking agents for IBS 22,28,30,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] (Table 2). Most of these trials were done between 1976 and 1994.…”
Section: Fiber Trialsmentioning
confidence: 99%
“…The episperm and collapsed layers from the seeds of Plantago ovata , the ispaghula seed husk, may be used instead in a dose of 4 to 20 g per day [26]. In a dose-finding study [27], 20 g  ispaghula seed husk was identified as possibly optimum daily dosage for treating IBS complaints. Lower doses were less effective.…”
Section: Discussionmentioning
confidence: 99%
“…At 10 g twice daily, bran was found to improve IBS symptoms, but the onset of efficacy was delayed until month 3 of treatment [14]. In clinical trials, psyllium and bran were well tolerated when initiated at the aforementioned maintenance doses, suggesting titration may not be necessary [13,14,15,16,17,18]; however, clinical experience with poor patient tolerance when no titration was performed suggests titration is important with fiber supplementation. Similarly, although adverse effects were found to be similar to placebo in clinical trials, patients were still at risk for adverse effects observed in persons without IBS, including abdominal pain, constipation, nausea, flatulence, and diarrhea.…”
Section: Resultsmentioning
confidence: 99%
“…Efficacious doses of psyllium ranged from 3 g twice daily to 6.4 g three times daily to 30 g once daily. Onset of efficacy with psyllium has occurred within 4 weeks of use [13,14]. At 10 g twice daily, bran was found to improve IBS symptoms, but the onset of efficacy was delayed until month 3 of treatment [14].…”
Section: Resultsmentioning
confidence: 99%